Superiority of Digital Reverse Transcription-PCR (RT-PCR) over Real-Time RT-PCR for Quantitation of Highly Divergent Human Rhinoviruses - Sedlak, Ruth Hall (J Clin Microbiol, 2017)
Human rhinoviruses (HRV) comprise 3 species representing more than 150 genotypes. As an important human respiratory pathogen, molecular detection is an indispensable tool for diagnosis and surveillance. However, the sequence diversity of HRV genotypes poses challenges for developing robust molecular methods that detect all genotypes with equal efficiencies. This study compares the accuracies of reverse transcription-quantitative PCR (RT-qPCR) and reverse transcription-digital PCR (RT-dPCR) for quantifying HRV RNA using genotype-specific primers and probes and a consensus primer/probe set targeting the 5′ noncoding region of HRV. When using consensus primers and probes for the quantification of HRV, RT-dPCR outperformed RT-qPCR by consistently and accurately quantifying HRV RNAs across more genotype groups, despite the presence of up to 2 target-sequence mismatches within the primer or probe binding region. Because it does not rely on amplification efficiency, which can be affected by sequence mismatches in primer/probe binding regions, RT-dPCR may be the optimal molecular method for future HRV quantification studies and for quantitating other viruses with high sequence diversity.